1980
DOI: 10.1071/sr9800163
|View full text |Cite
|
Sign up to set email alerts
|

Compaction of forest soils. A review

Abstract: The problem of soil compaction in forestry differs from that in agriculture because of differences in the nature of the crop, in particular the weight and size of the plant members and the length of time that they persist. The roots compact the soil as they increase in size, but they also transmit the weight of the tree and forces generated by the wind onto the soil. There are important differences in management practices; in forestry modern harvesting machines apply heavy loads and, for reasons of cost, tend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

25
376
0
17

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 583 publications
(418 citation statements)
references
References 28 publications
25
376
0
17
Order By: Relevance
“…Therefore, it is necessary for runoff and erosion control to exclude above human activity from plantations. Plant roots can secure loose soil, increase the waterholding capacity of soils, hold soils against erosion (Greacen and Sands, 1980) and supply organic matter for soil. Ross and Dykes (1996) found that removal of the root mat resulted in a six fold increase in runoff and soil loss compared to the intact forest floor.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary for runoff and erosion control to exclude above human activity from plantations. Plant roots can secure loose soil, increase the waterholding capacity of soils, hold soils against erosion (Greacen and Sands, 1980) and supply organic matter for soil. Ross and Dykes (1996) found that removal of the root mat resulted in a six fold increase in runoff and soil loss compared to the intact forest floor.…”
Section: Discussionmentioning
confidence: 99%
“…Wall and Heiskanen (2003) showed that air-filled porosity below 0.10 m 3 m -3 was associated with reduced growth of Norway spruce seedlings. Greacen and Sands (1980) cite a number of studies showing soil strength limitation occurring over a wide range of penetrometer resistance values (800 to 5000 kPa) for a variety of species and soil types. Although values reported as critical limits for root penetration depend on plant species, soil type, and how reduced root growth or plant response is defined, Bulmer (1998) used data from Greacen and Sands (1980) to calculate an average value of 2500 kPa as a limit beyond which plant roots appeared to have difficulty penetrating compacted soils.…”
mentioning
confidence: 99%
“…Greacen and Sands (1980) cite a number of studies showing soil strength limitation occurring over a wide range of penetrometer resistance values (800 to 5000 kPa) for a variety of species and soil types. Although values reported as critical limits for root penetration depend on plant species, soil type, and how reduced root growth or plant response is defined, Bulmer (1998) used data from Greacen and Sands (1980) to calculate an average value of 2500 kPa as a limit beyond which plant roots appeared to have difficulty penetrating compacted soils. In a recent study of LLWR effects on seedling growth, Siegel-Issem et al (2005) considered 2000 kPa as a growth limiting value for soil mechanical resistance, while Lipiec and Hakansson (2000) considered 3000 kPa as a limiting value in their investigations of compaction.…”
mentioning
confidence: 99%
“…Even though the impact of soil compaction on tree growth is species specific (Froehlich 1979;Greacen and Sands 1980), compaction of forest soils plays a major part in planning soil management strategies (Bulmer 1998;Page-Dumroese et al 2000 ). Soane (1990) defined compaction as a process of soil densification caused by the application of stresses usually of short duration.…”
mentioning
confidence: 99%